Standard costs for sowing and maintenance works in vegetable crops in the plain, hilly, mountains area - Mihaela Cristina Vlad (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
the paper presents the partial results obtained on the basis of the scientific researches carried out under the project "Specific cost-specific calculations for different types of agricultural holdings and profiles in the context of accessing the support of the NRDP 2014-2020". The project is financed by contract no. 1313 / 2015-2018, by the ADER research program of the Ministry of Agriculture and Rural Development. The standard costs for sowing, fertilizing, pruning, herbicide, phytosanitary treatments, depending on the crop area, type of farm, tractor power, and aggregate are highlighted.
Keywords: O13; O38; 330; standard costs; agricultural holdings